Molecular Biomarkers for the Evaluation of Colorectal Cancer: Guideline From the American Society for Clinical Pathology, College of American Pathologists, Association for Molecular Pathology, and American Society of Clinical Oncology. Issue 3 (6th February 2017) - Sepulveda, Antonia R.; Hamilton, Stanley R.; Allegra, Carmen J.; Grody, Wayne; Cushman-Vokoun, Allison M.; Funkhouser, William K.; Kopetz, Scott E.; Lieu, Christopher; Lindor, Noralane M.; Minsky, Bruce D.; Monzon, Federico A.; Sargent, Daniel J.; et al.
Abstract: Objectives: To develop evidence-based guideline recommendations through a systematic review of the literature to establish standard molecular biomarker testing of colorectal cancer (CRC) tissues to guide epidermal growth factor receptor (EGFR) therapies and conventional chemotherapy regimens. Methods: The American Society for Clinical Pathology, College of American Pathologists, Association for Molecular Pathology, and American Society of Clinical Oncology convened an expert panel to develop an evidence-based guideline to establish standard molecular biomarker testing and guide therapies for patients with CRC. A comprehensive literature search that included more than 4, 000 articles was conducted. Results: Twenty-one guideline statements were established. Conclusions: Evidence supports mutational testing for EGFR signaling pathway genes, since they provide clinically actionable information as negative predictors of benefit to anti-EGFR monoclonal antibody therapies for targeted therapy of CRC. Mutations in several of the biomarkers have clear prognostic value. Laboratory approaches to operationalize CRC molecular testing are presented.